Spontaneous regression of port-wine stain. - Milano, A. (European Journal of Pediatric Dermatology, 2022)
Port wine stain (PWS) is a more or less extensive capillary malformation present at birth, often unilateral, and sometimes associated with ocular and/or cerebral malformations; histologically, it is characterized by a vasodilation of the superficial capillaries of the papillary dermis. PWS has a prevalence of 3 in 1,000 cases (4). The often segmental distribution of the face is due to a somatic mutation, usually in the GNAQ (6) gene, which codes for the Gαq protein. The latter is involved in the function of various growth factors, vasoactive peptides and neurotransmitters; the GNAQ mutation affects a neuroectodermal cell of the optic vesicle or placode (neuroectodermal thickening) that will then give rise to the anterior brain (...).